Effect of Indirect Advertising and Promotion Activities of Tobacco Products in Khulna - Qazi Azad-uz-zaman; Quazi Zahangir Hossain (Intelektual Pustaka Media Utama, 2014)
Different forms of tobacco advertisement and promotional activities are the burden of tobacco epidemic in Bangladesh. A descriptive type of cross-sectional study was carried out on a total of 404 adults, randomly selected from urban and rural areas. Data were collected implementing both qualitative and quantitative methods from July to September 2013 and found 52% of the respondents were smoking cigarette or bidi, within them only 30% of the male adults were never user of tobacco of any kind. The respondents mainly noticed packet wall (52%), posters (65%), and big size packets (38%) as indirect advertisement as well as free sample (51%) and free gifts (43%) as promotional activities. A significant effect was identified of the activities on increasing consumption which tobacco control advocates and practitioners always argue. Existing laws do not allow giving free samples and free gift to persons, it should be enforced adequately as well as all tobacco control activists should be vigilant on unlawful activities of tobacco traders.